The social and economic impact of international female migration on left-behind parents in East Java, Indonesia. (March 2019) - Aminuddin, M. Faishal; Pallikadavath, Saseendran; Kamanda, Amie; Sukesi, Keppi; Rosalinda, Henny; Hatton, Kieron
The objective of this article is to examine the impact of international female labor migration on left-behind parents by taking into consideration the daughters' marital status. Data were taken from in-depth interviews with 37 left-behind parents of migrant women in East Java Province. The study showed that left-behind parents had limited access to the remittances sent by married daughters, except when they carried out childcare responsibilities. Parents of unmarried daughters had some access to remittances, but this varied according to the economic conditions of the family. Left-behind parents were concerned about the safety of their daughters overseas, the marriage prospects of unmarried daughters, the stability of their daughters' marriages and the welfare of left-behind grandchildren. Because the migration of married and unmarried daughters has diverse impacts on left-behind parents, this should be considered in programs that aim to mitigate potential negative impacts of women's migration.